1973
DOI: 10.1002/app.1973.070170414
|View full text |Cite
|
Sign up to set email alerts
|

A deformational mechanism in particulate-filled glassy polymers

Abstract: SynopsisThe stress-strain behavior of glass bead-filled polystyrene, styrene-acrylonitrile, styrene-acrylonitrile-butadiene, and polyphenglene oxide composites is studied at various temperatures below their glass transition temperature. Earlier studies of beadfilled composites indicated that the addition of filler decreases toughness and ultimate elongation. Our results show that while this is true for certain conditions, it is also possible for such composites to have higher toughness and ultimate elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 1 publication
1
28
0
Order By: Relevance
“…This study has been reported by some researchers [22][23][24]. Based on Table 1, the tensile strength of EP-modified CS/CC is the highest as compared to ADP-modified CS/CC and GLA-modified CS/CC biocomposite films.…”
Section: Tensile Propertiesmentioning
confidence: 56%
“…This study has been reported by some researchers [22][23][24]. Based on Table 1, the tensile strength of EP-modified CS/CC is the highest as compared to ADP-modified CS/CC and GLA-modified CS/CC biocomposite films.…”
Section: Tensile Propertiesmentioning
confidence: 56%
“…In coupled systems, the knee on the stress-strain curve is more difficult to locate, and sometimes the knee does not show up at all (see Table 1 in ref. 3). A comparison of UD values for coupled and corresponding decoupled systems has given the following results: ABS, 2330 and 1750 psi (ratio = 1.33); PVC, 2960 and 1870 psi (ratio = 1.58); PMMA, 2790 and 2350 psi (ratio = 1.19); and CAB, 1430 and 1430 psi, respectively (ratio = 1.0).…”
Section: Resultsmentioning
confidence: 97%
“…113 The constants C and D can be determined from the following boundary conditions By applying the above boundary conditions we find Substitution of the above values into Equation (17) results in or for the stress developed in the ith fiber,…”
Section: Stress Distribution Along a Particle Diametermentioning
confidence: 99%